Robot‐assisted partial nephrectomy for large renal masses: a multi‐institutional series. (1st March 2018) - Delto, Joan C.; Paulucci, David; Helbig, Michael W.; Badani, Ketan K.; Eun, Daniel; Porter, James; Abaza, Ronney; Hemal, Ashok K.; Bhandari, Akshay
Abstract : Objectives: To compare peri‐operative outcomes after robot‐assisted partial nephrectomy (RAPN) for cT2a (7 to <10 cm) to cT1 tumours. Materials and Methods: Patients with a cT1a ( n = 1 358, 76.4%), cT1b ( n = 379, 21.3%) or cT2a ( n = 41, 2.3%) renal mass were identified from a multi‐institutional RAPN database. Intra‐ and postoperative outcomes were compared for cT2a masses vs cT1a and cT1b masses using multivariable regression models (linear, logistic, Poisson etc.), adjusting for operating surgeon and a modified R.E.N.A.L. nephrometry score that excluded the radius component. Results: The median sizes for cT1a, cT1b and cT2a tumours were 2.5, 5.0 and 8.0 cm, respectively ( P < 0.001) with modified R.E.N.A.L. nephrometry scores being 6.0, 6.5 and 7.0, respectively (cT1a, P < 0.001; cT1b, P = 0.105). RAPN for cT2a vs cT1a masses was associated with a 12% increase in operating time ( P < 0.001), a 32% increase in estimated blood loss ( P < 0.001), a 7% increase in ischaemia time ( P = 0.008), a 3.93 higher odds of acute kidney injury at discharge (95% confidence interval [CI] 1.33, 8.76; P = 0.009) and a higher risk of recurrence (hazard ratio [HR] 10.9, 95% CI 1.31, 92.2; P = 0.027). RAPN for cT2a vs cT1b masses was associated with a 12% increase in blood loss ( P = 0.036), a 5% increase in operating time ( P = 0.062) and a marginally higher risk of recurrence (HR 11.2, 95% CI 0.77, 11.5; P = 0.059). RAPN for cT2a tumours was not associated with differences in complications (cT1a, P = 0.535; cT1b, P = 0.382), positive margins (cT1a, P = 0.972; cT1b, P = 0.681), length of stay (cT1a, P = 0.507; cT1b, P = 0.513) or renal function decline up to 24 months post‐RAPN (cT1a, P = 0.124; cT1b, P = 0.467). Conclusion: For T2a tumours RAPN is a feasible treatment option in a select patient population when performed by experienced surgeons in institutions equipped to manage postoperative complications. Although RAPN was associated with greater blood loss and longer operating and ischaemia time in T2a tumours, it was not associated with greater complication or positive surgical margin rates compared with T1 tumours. Renal function preservation rates were equivalent for up to 24 months postoperatively; however, 12‐month recurrence‐free survival was significantly lower in the T2a group. Extended follow‐up is required to further evaluate long‐term survival.